2020
DOI: 10.1111/liv.14666
|View full text |Cite
|
Sign up to set email alerts
|

GES: A validated simple score to predict the risk of HCC in patients with HCV‐GT4‐associated advanced liver fibrosis after oral antivirals

Abstract: Background & Aims: Hepatocellular carcinoma (HCC) risk persists after hepatitis C virus (HCV) eradication with direct-acting antivirals (DAAs), particularly in patients with cirrhosis. Identifying those who are likely to develop HCC is a critical unmet medical need. Our aim is to develop a score that offers individualized patient HCC risk prediction. Methods: This two-centre prospective study included 4400 patients, with cirrhosis and advanced fibrosis who achieved a sustained virologic response (SVR), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 16 publications
1
49
0
2
Order By: Relevance
“…Although previous studies reported that the size of NHHN is associated with hypervascularisation, 8 this association was not observed in this study, even though the size of NHHNs increased with hypervascularisation. In contrast, serum AFP levels, a reported risk factor for HCC development after SVR, 15‐17 were significantly higher in patients whose NHHNs hypervascularised than in patients whose NHHNs did not.…”
Section: Discussionmentioning
confidence: 74%
“…Although previous studies reported that the size of NHHN is associated with hypervascularisation, 8 this association was not observed in this study, even though the size of NHHNs increased with hypervascularisation. In contrast, serum AFP levels, a reported risk factor for HCC development after SVR, 15‐17 were significantly higher in patients whose NHHNs hypervascularised than in patients whose NHHNs did not.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, 5 authors reported data on patients with advanced fibrosis, defined through histology (F3-F4), non-invasive tests or criteria for chronic advanced liver disease (cACLD) 11 , 36 , 43–46 ( Table 2 ). Eight out of these studies enrolled only patients with an SVR, 10 , 21 , 30 , 33 , 37 , 44–46 whilst in one study data could be extrapolated. 34 In studies including also non-SVR patients, rates of treatment failure ranged between 1.9% and 10% ( Table 2 ).…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
“… 38 Thus, among indirect markers of PH were both biochemical tests and clinical features. For example, albumin 20 , 31 , 37 , 44 , 45 and PLT 20 , 21 , 27 , 29 were independently associated with HCC occurrence, either as single predictors or when included in predictive scores ( Tables 6 and 7 ). The presence of esophageal varices (EV) 28 or ascites was associated with an increased the risk of de-novo HCC.…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
“…der "AST to platelet ratio index" (APRI; [34,[39][40][41]), eine niedrige Thrombozytenzahl als Marker der portalen Hypertension [33,46] sowie ein niedriges Serumalbumin als Maß der reduzierten Lebersynthe-seleistung, waren mit einem erhöhten HCC-Risiko assoziiert [7,33]. Letztendlich zeigte auch das α-Fetoprotein (AFP), ein in Österreich häufig angewandter Biomarker/Tumormarker für das Vorliegen eines HCC, einen prädiktiven Wert [39,43,[47][48][49]. Bezüglich aller dieser Parameter bleibt jedoch abzuwarten, welche Kombination(en) schlussendlich die höchste Genauigkeit aufweisen werden.…”
Section: Hcc-entwicklungunclassified
“…Bezüglich aller dieser Parameter bleibt jedoch abzuwarten, welche Kombination(en) schlussendlich die höchste Genauigkeit aufweisen werden. Hier konnte bereits eine Arbeit aus Ägypten eine große Studienpopulation anhand des Geschlechts (männlich), Alters (≥54 Jahre), Fibrosestadiums, Serumalbumins (<3,8 g/dl) und des AFP(>20 ng/ml) in 3 Risikogruppen mit unterschiedlich hohem HCC-Risiko einteilen [47]. Eine andere Studie aus Spanien entwarf 2 Scores, die jeweils eine gute Vorhersagekraft bezüglich HCC aufwiesen.…”
Section: Hcc-entwicklungunclassified